IMPROVEMENT OF SPEAKING SKILLS THROUGH THE APPLICATION OF TALKING STICK MODEL IN FIFTH GRADE STUDENTS OF KUTOWINANGUN 04 ELEMENTARY SCHOOL - Erni Palupi; Firosalia Kristin (Universitas Negeri Medan, 2019)
Abstract: Improvement Of Speaking Skills Through The Application Of Talking Stick Model In Fifth Grade Students Of Kutowinangun 04 Elementary School. This study aims to improve speaking skills through the application of the Talking Stick model in fifth grade students of Kutowinangun 04 Elementary School. This type of research is Classroom Action Research (PTK) with research subjects in fifth grade students of Kutowinangun 04 Elementary School consisting of 18 male students and 11 female students. The data collection technique used is observation. The procedure of action research consists of two cycles. Each cycle through four stages of research includes: planning, action, observation, and reflection. The data analysis technique used quantitative descriptive and qualitative descriptive. The results showed an increase in the percentage of the average value of students' speaking skills by category in the first cycle, which was equal to 11.56%, with the initial conditions 58.10% (categories need guidance) increased to 69.66% (sufficient category). In the second cycle, an increase of 15.34%, with an initial condition of 69.66% (sufficient category) increased to 85% (good category). The percentage of completeness of speaking skills showed that in pre-action as many as 5 students completed (17.24%), increased to 18 students completed (62.07%) in the first cycle, and increased to 29 students completed (100%) in cycle II. Thus, through the application of the Talking Stick model can improve the learning skills of fifth grade students of Kutowinangun 04 Elementary School. Keywords: Improving Student Speaking Skills, Talking Stick Model Abstrak: Peningkatan Keterampilan Berbicara Melalui Penerapan Model Pembelajaran Talking Stick Pada Siswa Kelas 5 SD Ktowinangun 04. Penelitian ini bertujuan untuk meningkatkan keterampilan berbicara melalui penerapan model pembelajaran Talking Stick pada siswa Kelas 5 SD Negeri Kutowinangun 04 Salatiga. Jenis penelitian ini adalah Penelitian Tindakan Kelas (PTK) dengan subjek penelitian siswa kelas 5 SD Negeri Kutowinangun 04 yang terdiri dari 18 siswa laki-laki dan 11 siswa perempuan. Teknik pengumpulan data yang digunakan adalah observasi. Prosedur penelitian tindakan terdiri dari dua siklus. Setiap siklus melalui empat tahap penelitian diantaranya: perencanaan, tindakan, observasi, dan refleksi. Teknik analisis data yang digunakan berupa deskriptif kuantitatif dan deskriptif kualitatif. Hasil penelitian menunjukkan terjadi peningkatan persentase nilai rata-rata keterampilan berbicara siswa berdasarkan kategori pada siklus I, yaitu sebesar 11,56%, dengan kondisi awal 58,10% (kategori perlu bimbingan) meningkat menjadi 69,66% (kategori cukup). Pada siklus II, terjadi peningkatan sebesar 15,34%, dengan kondisi awal 69,66% (kategori cukup) meningkat menjadi 85% (kategori baik). Persentase ketuntasan keterampilan berbicara menunjukkan bahwa pada pratindakan sebanyak 5 siswa tuntas (17,24%), meningkat menjadi 18 siswa tuntas (62,07%) pada siklus I, dan meningkat menjadi 29 siswa tuntas (100%) pada siklus II. Dengan demikian, melalui penerapan model pembelajaran Talking Stick dapat meningkatkan keterampilan belajar siswa kelas 5 SD Kutowinangun 04. Kata Kunci: Peningkatan Keterampilan Berbicara Siswa, Model Pembelajaran Talking Stick